The Role of Organisational Culture in Digital Transformation in the South African Retail Sector - Lehabe, Malebo Lily (University of the Witwatersrand, Johannesburg, 2024)
The aim of this study is to identify the role of organisational culture in the South African retail sector and determine how it affects digital transformation. The study considers the state of digital transformation in the South African retail sector, the role of organisational culture and the attributes that hinder and propel the success of digital transformation. COVID-19 accelerated disruption in the retail sector, and retailers were compelled to transform digitally. This is a qualitative study that focuses on Fast Moving Consumer Goods in the retail sector. Diverse entities were considered regardless of size or digital maturity. The Westerman Framework was the aspect of digital maturity. It was found that the South African retail sector is in its infancy regarding digital maturity and that retail entities could not provide evidence of the importance of organisational culture. Organisational culture attributes that enable and hinder success and those that currently hinder the success of digital transformation were also considered to understand the impact these attributes have on digital transformation.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, In the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Digital Culture; Digital Transformation; Organisational Culture; Retail Sector; SDG-9: Industry, innovation and infrastructure